1988
DOI: 10.1007/bf00320754
|View full text |Cite
|
Sign up to set email alerts
|

In vivo recovery and half-life time of a steam-treated factor IX concentrate in hemophilia B patients

Abstract: Factor IX (FIX) recovery and half-life was measured in ten hemophilia B patients under standardized conditions. Each patient received a steam-treated high-purity factor IX concentrate at a dose of 19-39 U/kg body weight. FIX activity was determined using a one-stage assay, which was calibrated against the international concentrate standard (reagents from Immuno, Heidelberg). The in vivo recovery ranged from 24% to 53% (mean value 37.7%) and the half-disappearance time (HDT) from 8-30 h (mean 16.7 h). In four o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…In a study on F VIII (14), we have shown this method of volume estimation to minimize interindividual variation in IVR. In published reports, representative mean values of IVR (calculated as in this study) range between 35 and 68% (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In a study on F VIII (14), we have shown this method of volume estimation to minimize interindividual variation in IVR. In published reports, representative mean values of IVR (calculated as in this study) range between 35 and 68% (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 82%
“…In all cases the dose of F IX was about 50 IU/kg body weight (labeled activity) and the infusion time was 10 min. Venous blood was collected into tubes containing 0.129 M sodium citrate 1 :9 before and at 0 (5,10,15,20), 30 (45) min, 1 (2),3,6,9,12,24 (32), 48 and (72) h after the end of the injection. (Sampling times in parentheses were not used in the Immunine/Prothromplex study).…”
Section: Clinical Materials and In Vivo Studiesmentioning
confidence: 99%
“…In studies in which only one sample was taken beyond 24 h, the estimate of the terminal tl/2 becomes very dependent on this single FIX:C value. In contrast, studies with shorter sampling periods normally report a shorter halflife and a higher clearance (Zauber et al 1977;Heldebrant et al 1985;Longo et al 1987;Goldsmith et al 1992;Kim et al 1992;Berntorp et al 1993), although there are some ex-ceptions to this general observation (K6hler et al 1988;Kim et al 1990). The model-independent parameters also show large variances.…”
Section: Sampling Time and Parameter Valuesmentioning
confidence: 98%
“…In one study, a two-fold difference in Factor IX level from the same plasma sample and a 1.4-fold difference in the amount of clotting factor in the administered dose was apparent from the assays. 17 With relatively infrequent immediate postinfusion sampling, the rapid alpha-phase of disappearance from the plasma compartment is highly variable; however, a beta-phase of elimination of around 27 hours is more consistently found. 16 To predict dosage requirements from coagulation assay-based kinetic studies, an intermediate direct half-life calculation is useful.…”
Section: Infusion Kineticsmentioning
confidence: 99%
“…18 In the latter, initial (15 minute) recovery averaged 35% of the injected dose and the alpha-phase of disappearance was shorter than data following most concentrate infusions. This number varies somewhat with different kinetic models, but major differences are likely due to variability in the clotting assays, 17 presence of activated and inactive forms, and Goldsmith et al, 71 1992 Kohler et al, 17 1988 Zauber and Levin, 16 1977 Goldsmith et al, 71 1992 Kasper et al, 60 1991 Kasperetal, 60 1991 Kim et al, 69 1991 Smith and Factor IX is somewhat smaller than albumin, so that its volume of distribution should reflect both the intravascular and extravascular compartments. Although the low initial recovery is on the order expected following equilibration with the extravascular space, it is unlikely that this equilibration would have had time to occur within the 15 minutes between infusion and postinfusion sampling.…”
Section: Infusion Kineticsmentioning
confidence: 99%